2020
DOI: 10.1111/ijag.15843
|View full text |Cite
|
Sign up to set email alerts
|

Chemical durability of lead crystal glass: Comparison of short‐term aqueous and atmospheric alteration at 90°C

Abstract: Crystal glass alteration in an aqueous medium has been extensively studied following the implementation of strict regulations regarding lead leaching. However, despite the widespread use of lead glasses and crystal glass by artists and artisans ever since antiquity, few works focus on crystal glass corrosion in atmospheric conditions. In this preliminary study, the altered layers formed on crystal glass in aqueous and atmospheric conditions at 90°C are compared. On the timescale studied (20 days), ToF-SIMS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…However, some studies have argued that glass alteration in vapor phase is distinct to glass alteration in aqueous medium because of some vapor-phase alteration mechanisms like "glass hydration without dealkalization," which were not encountered in studies of glass alteration in aqueous medium and other aqueous alteration mechanisms like "repolymerization," which have not yet been observed in vapor phase conditions. It has been suggested that the chemical properties of the glass-water system are modified with the alteration conditions 58,59 . Nevertheless, the understanding gained on aqueous alteration of glasses has been useful to understand glass alteration in vapor phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have argued that glass alteration in vapor phase is distinct to glass alteration in aqueous medium because of some vapor-phase alteration mechanisms like "glass hydration without dealkalization," which were not encountered in studies of glass alteration in aqueous medium and other aqueous alteration mechanisms like "repolymerization," which have not yet been observed in vapor phase conditions. It has been suggested that the chemical properties of the glass-water system are modified with the alteration conditions 58,59 . Nevertheless, the understanding gained on aqueous alteration of glasses has been useful to understand glass alteration in vapor phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in the pharmaceutical industry highlighted challenges regarding sustainable packaging of drugs derived from new molecular entities and delicate active pharmaceutical ingredients. , A commentary published during the first few months of the COVID-19 pandemic underscored the enormous need for billions of vials to contain coronavirus vaccine doses and praised the appropriateness of glass, the primary packaging of choice, particularly due to its superior long-term storage and low gas permeability . Nonetheless, silicate glass is chemically reactive vis à vis aqueous phases despite its apparent chemical inertness. , This extremely slow but inexorable glass surface dissolution can adopt different mechanisms of ion exchange and surface hydration, which leads from alkali-depleted layers, up to hydrolysis of the silicon–oxygen bonds, subsequently inducing thickness loss by network dissolution, especially in basic media. These mechanisms depend not only on the glass composition and network structure but also on the solution in contact with the glass surface. Reactive excipient solutions in which molecular entities are conditioned can still interact aggressively with the glass container, altering the glass surface, and ultimately producing a silica-rich gel layer likely to detach from the surface, or precipitate particles from the ions in solution and constituents of the drug product, pitting, or glass flakes (lamellae) through delamination, as exemplified by the photograph of Figure A.…”
Section: Introductionmentioning
confidence: 99%